Electric-charge-dependent directed flow splitting of produced quarks in Au+Au collisions - Aboona, Bassam; Deppner, Ingo Martin; Leung, Yue; Söhngen, Yannick (Physics letters, 2025)
We report directed flow (v1) of multistrange baryons (Ξ and Ω) and improved v1 data for K−, p¯, Λ¯ and ϕ in Au+Au collisions at sNN=27 and 200 GeV from the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). We focus on particles whose constituent quarks are not transported from the incoming nuclei but instead are produced in the collisions. At intermediate impact parameters, we examine quark coalescence behavior for particle combinations with identical quark content, and search for any departure from this behavior (“splitting”) for combinations having non-identical quark content. Under the assumption of quark coalescence for produced quarks, the splitting strength appears to increase with the electric charge difference of the constituent quarks in the combinations, consistent with electromagnetic effect expectations.
Online verfügbar: 17. Januar 2025, Artikelversion: 27. Januar 2025
*The STAR Collaboration: B.E.Aboona, I.M. Deppner, Y.H. Leung, Y. Söhngen [und 347 weitere Personen]
Gesehen am 14.10.2025